Microhardness of nanofilled composite resin light-cured by LED or QTH units with different times - Ana Isabelle Salvador Groninger; Giulliana Panfiglio Soares; Robson Tetsuo Sasaki; Glaucia Maria Bovi Ambrosano; José Roberto Lovadino; Flávio Henrique Baggio Aguiar (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the influence of light-curing units and light-curing time on the microhardness of a nanofilled composite resin. Methods: Forty-five composite resin (Z350 - 3M) specimens were randomly prepared using Teflon ring molds (4.0 mm internal diameter and 2 mm depth) and divided into nine experimental groups (n=5): three polymerization units (conventional - 450 mW/ cm2 ; 2nd generation LED - 1100 mW/cm2 ; and 3rd generation LED - 700 mW/cm2 ) and three lightcuring times (20 s, 40 s, and 60 s). All specimens were polymerized with the light-curing tip positioned 8 mm far from the top surface of the specimen. After 24 h, Knoop microhardness measurements were made on the top and bottom surfaces of the specimen, with a load of 10 g for 10 s. Five indentations were made on each surface. All results were analyzed statistically by subdivided parcel ANOVA (Split-Plot) and Tukey's tests (p<0.05). Results: There were no statistically significant differences for the polymerization unit and light-curing time factors in either top or bottom surface. For all experimental conditions, the top surfaces showed greater hardness than the bottom surfaces (p<0.0001). Conclusions: The mode of polymerization and the lightcuring time did not affect the hardness of the nanofilled composite resin, and increasing the lightcuring time did not improve the hardness of the bottom surface of the composite resin.